TRANFORMASI KELEMBAGAAN PESANTREN TREMAS ADAPTASI DAN INOVASI DI ERA DIGITAL - Maftuhah; Khoeron; Tobroni; Faridi (STIT Muhammadiyah Paciran Lamongan, 2025)
Pesantren Tremas Pacitan, one of the oldest Islamic educational institutions in Indonesia, has made significant contributions to the formation of scholars and religious leaders for over two centuries. However, the currents of modernization and global development pose significant challenges in maintaining its relevance and effectiveness as an educational institution. This research aims to analyze the institutional transformation of Pesantren Tremas through curriculum adaptation, technology, economic independence, and institutional management to respond to these challenges. Using qualitative methods with a case study approach, data were obtained through interviews, observations, and document analysis. The research results show that the pesantren have integrated religious and general education, utilized technology in learning and digital preaching, developed independent business units, and adopted modern management practices. Although there are obstacles such as resistance to change and limited infrastructure, this transformation strengthens the competitiveness of pesantren in the era of globalization. This research concludes that such strategic adaptation can serve as a model for other pesantren in maintaining the balance between innovation and the preservation of traditional Islamic values.